Development of online shopping with management system using hybrid mobile application / Zulhilmi Mohd Zahid - Mohd Zahid, Zulhilmi (2017)
Rm30Shop Company is an online shop that provides a shopping platform in Malaysia, particularly through Instagram. Rm30Shop activities range of a series of sales, review services, fashion trend which focuses business activity with the customer. Through an observation that has been conducted, it is found out that there is an inefficiency of data management during a buy and sells activities, whereby one of the activities in the shop; data management of customer and taking orders process is still using the manual process. The current way of doing the data management of orders, product, customers in the shop is through log book, in which the log book reduce the effectiveness and efficiency of the shop and sometimes it might be unorganized and may results in information mixed-up. Additionally, the shop encountered a challenge to enhance the medium to advertise their product to the world. They currently make sell using Instagram which is the only resource to use for advertising. The motivation that drives to the construction of this project is to develop a Hybrid mobile application that will handle the data management aspect besides providing the ability to produce cross platform apps using a single set of work which makes the shop has a wider resource as a medium to advertise and overall enhanced their profit. Moreover, it has been found out during the interview conducted that there is no system has yet to be developed to assist the process. The first objective of the project is to gather and analyze the requirement of Online Shopping with Management System for Rm30Shop. Second objective is to design the application for Rm30Shop. The final objective of this project to develop the application for Rm30Shop. The significance of this project would be to help academician to analyse the development of Hybrid Mobile Application process in a more orderly manner as such the massive amount of data will be more efficient to be used using an ICT-based tool rather than manually. The methodology used to develop this project is the Modified Waterfall System Development Life Cycle, which contains 3 phases; Requirement Gathering and Analysis, Design, and Implementation phase. One of the deliverables from the phases is the Software Requirements Specifications that will be the basis for producing the design documentation. This work can be further extended in the concept of Human-Computer Interaction (HCI) elements to enhance the user experience and make it more interactive.